2015
DOI: 10.1371/journal.pone.0142559
|View full text |Cite
|
Sign up to set email alerts
|

A Faster Triphosphorylation Ribozyme

Abstract: In support of the RNA world hypothesis, previous studies identified trimetaphosphate (Tmp) as a plausible energy source for RNA world organisms. In one of these studies, catalytic RNAs (ribozymes) that catalyze the triphosphorylation of RNA 5'-hydroxyl groups using Tmp were obtained by in vitro selection. One ribozyme (TPR1) was analyzed in more detail. TPR1 catalyzes the triphosphorylation reaction to a rate of 0.013 min-1 under selection conditions (50 mM Tmp, 100 mM MgCl2, 22°C). To identify a triphosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…We did not expect that the complete removal of the P5 stem would lead to functional ribozymes. 35 However, the fragmented ribozyme variants with truncated P5 duplex were fully functional, and two of them -with a P5 stem length of 2 and 3 base pairswere even faster than the ribozyme with a full P5 duplex (Fig. 3B).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We did not expect that the complete removal of the P5 stem would lead to functional ribozymes. 35 However, the fragmented ribozyme variants with truncated P5 duplex were fully functional, and two of them -with a P5 stem length of 2 and 3 base pairswere even faster than the ribozyme with a full P5 duplex (Fig. 3B).…”
Section: Discussionmentioning
confidence: 91%
“…This reduction suggested that the P5 helix fulfills a function during the triphosphorylation reaction, presumably by favoring the catalytically active conformation. On the other hand, the triphosphorylation rate of 0.15 min À1 for the construct without P5 helix (as compared to 0.31 min À1 for the parental construct 35 ) showed that structural elements can not only be reduced in length but also be completely omitted while maintaining a functional ribozyme.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, the Spinach2 aptamer [5] regulates the fluorescence of a fluorophore via binding, providing an interesting alternative to GFP tagging. In vitro selection has been applied to discover a variety of ribozymes [6], deoxyribozymes [7], aptazymes [8], and riboswitches [9]. With appropriate polymerase enzymes, selection experiments can even be done with non-natural nucleic acids, as shown for a series of xeno-nucleic acids (XNAs).…”
Section: In Vitro Evolution and Fitness Landscapes Of Nucleic Acidsmentioning
confidence: 99%